Indian spooks: What Hindi Comic Books Readers Are Afraid of - Marcin Ciemniewski (Ksiegarnia Akademicka Publishing, 2019)
The comic book industry in India began in 1950. Back then leading American comic books like The Phantom, Flash Gordon and Rip Kirby started to be published in India and translated into local languages. Indian youngsters in no time became interested in the new medium, especially in superhero comics known from the American popular culture. The success of these translations encouraged local publishers and cartoonists to create Indian themed comic books, set in India with Indian heroes (and superheroes) − even though Indian comics were still strongly influenced by American ones, mainly in terms of esthetics. However, around 1950, American comics publishing companies also tried to attract adult readers by presenting more adult content in a form of horror and thriller stories. Publishers in India quickly adapted this trend launching a very popular comic book series in Hindi of thrill, horror and suspense. In this way horror – till then almost completely absent from Indian literature and popular culture – was introduced to the local audience. The question remains, how different are those local spooks from the American ones and finally: what are Indians afraid of?